rTMS Therapy for Eating Disorders: Scoping Review on Efficacy, Safety, Stimulation Parameters and Study Subjects. - Takahashi, Shun; Ikeda, Shunichiro; Ueda, Masaya; Harada, Tomoko; Ishii, Ryouhei (European Eating Disorders Review, 2026)
Objective: Repetitive transcranial magnetic stimulation (rTMS) has potential as a therapeutic tool for eating disorders. In this scoping review, we examine the efficacy and safety of rTMS therapy for eating disorders besides stimulation parameters and the clinical statuses of participants. Method: Following PRISMA‐ScR framework, we searched four databases (PubMed, Scopus, Web of Science and PsycInfo) to review clinical interventional studies using rTMS for patients with eating disorders. Results: Thirty‐two studies were included. Benefits of rTMS on mood or eating disorder symptoms were reported for patients with anorexia nervosa. Meanwhile, there was improvement in binge eating and impulsivity in patients with bulimia nervosa, but without statistical significance in randomised controlled studies. There were no serious adverse events in relation to rTMS therapy. Stimulation of the left dorsolateral prefrontal cortex at high frequency with 20,000 stimulations was shown to be widely adopted in research on rTMS therapy for eating disorders. Conclusion: The number of pulses to the left dorsolateral prefrontal cortex may have been insufficient. The dorsomedial prefrontal cortex is suggested to be an effective stimulation site for patients with binge‐purge symptoms. Future research should focus on optimising stimulation parameters including the frequency, the intensity, the session number, and the stimulation site. Highlights: Preferable effects of rTMS therapy on mood or eating disorder symptoms have been reported in various papers, but few effects were seen on weight gain in patients with anorexia nervosa.The dorsomedial prefrontal cortex is expected to be an effective stimulation site for binge‐purge symptoms in patients with eating disorders.Future research should focus on optimising stimulation parameters tailored to the specific symptom domains and subtypes of eating disorders.